Leber's Hereditary Optic Neuropathy: A Report on Novel mtDNA Pathogenic Variants - Peverelli, Lorenzo; Catania, Alessia; Marchet, Silvia; Ciasca, Paola; Cammarata, Gabriella; Melzi, Lisa; Bellino, Antonella; Fancellu, Roberto; Lamantea, Eleonora; Capristo, Mariantonietta; Caporali, Leonardo; La Morgia, Chiara; et al. (Frontiers in Neurology, 2021)
Leber's hereditary optic neuropathy (LHON) is due to missense point mutations affecting mitochondrial DNA (mtDNA); 90% of cases harbor the m.3460G>A, m.11778G>A, and m.14484T>C primary mutations. Here, we report and discuss five families with patients affected by symptomatic LHON, in which we found five novel mtDNA variants. Remarkably, these mtDNA variants are located in complex I genes, though without strong deleterious effect on respiration in cellular models: this finding is likely linked to the tissue specificity of LHON. This study observes that in the case of a strong clinical suspicion of LHON, it is recommended to analyze the whole mtDNA sequence, since new rare mtDNA pathogenic variants causing LHON are increasingly identified.